2012
DOI: 10.15845/voices.v12i3.647
|View full text |Cite
|
Sign up to set email alerts
|

Professional Competences of Music Therapists Working in Post-stroke Rehabilitation

Abstract: The aim of this qualitative study is to gain more insight into the skills and knowledge that music therapists feel they need, in order to work successfully with people who have had an acute stroke. For this purpose, six music therapists were interviewed about their own particular specialist education. Another interview topic for them was to recount their subjective experiences of poststroke rehabilitation work in hospitals and health care units during the course of two projects that they participated in. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…There is also some indication that clients find verbal processing in music therapy useful. Results of an investigation of music therapists working in post-stroke rehabilitation showed that both the therapists and clients viewed the interaction (i.e., discussion) with clients as the most important factor in keeping sessions therapeutic (Forsblom & Ala-Ruona, 2012). Paulander's study (as cited in Lindblad, 2016) showed that verbal processing in music therapy enables clients to process, understand, and give meaning to their musical experiences.…”
mentioning
confidence: 99%
“…There is also some indication that clients find verbal processing in music therapy useful. Results of an investigation of music therapists working in post-stroke rehabilitation showed that both the therapists and clients viewed the interaction (i.e., discussion) with clients as the most important factor in keeping sessions therapeutic (Forsblom & Ala-Ruona, 2012). Paulander's study (as cited in Lindblad, 2016) showed that verbal processing in music therapy enables clients to process, understand, and give meaning to their musical experiences.…”
mentioning
confidence: 99%
“…As CoMT approaches become more common, these types of crossovers may also be more common and may even be considered a strength. Similarly, Forsblom and Ala-Ruona (2012) found in their study on music therapy with adults with an acquired brain injury that being more personal with their clients helped the therapeutic process. This was a major influence on the clients' experience and how much they were engaged in their therapy process.…”
Section: Self-disclosurementioning
confidence: 95%
“…The assumption that humour, or a sense of humour as a personal characteristic, was not only a sign of wellbeing but also enabled healthy social interactions was widespread (Bright, 2010;Christenbury, 2017;Cobbett, 2016;Dennis & Rickson, 2014;Dwyer, 2007;Finch et al, 2016;Forsblom & Ala-Ruona, 2012;Frank, 2005;Hitchen et al, 2010;Melhuish, 2013;Mitchell, 2017;Pavlicevic, 2001;Potvin et al, 2018;Ridder & McDermott, 2014;Roberts, 2006;Rowland & Read, 2011). Lichtensztejn et al (2014) went as far as to document a client's responses to humour in music therapy to aid formal assessments of cognitive capacity and Geretsegger et al (2015) also identified humour as being important in ascertaining the level of participation when working with a child in music therapy.…”
Section: A Sense Of Humourmentioning
confidence: 99%